Coupled simulation of groundwater flow and multispecies reactive transport in an unconfined aquifer using the element-free Galerkin method. (December 2020) - Pathania, Tinesh; Eldho, T.I.; Bottacin-Busolin, Andrea
Highlights: We demonstrate the element-free Galerkin method (EFGM) to simulate groundwater flow and multispecies reactive transport. EFGM is less affected by numerical dispersion compared to FEM. The proposed model is capable of solving the multispecies transport equations with space or time-dependent transport parameters. Good application potential of the developed model in simulating the reactive transport in large field aquifers. Abstract: In this paper, the meshless element-free Galerkin method (EFGM) based coupled model is developed to simulate the groundwater flow and multispecies reactive transport coupled with sequential decay reactions in unconfined aquifers. The use of moving least squares (MLS) approximation in approximating the head and concentration variables in EFGM tends to provide the solutions with better numerically stability than the finite difference (FDM) and finite element methods (FEM). Therefore, the proposed model is less affected by numerical dispersion unlike FDM/FEM based models. For the validation of the proposed model, it is applied to multispecies transport equations coupled with sequential reactions, reversible reactions, spatially or temporally varying transport velocities, time dependent decay rates and species concentration at the boundaries. EFGM solution is matching very well with the available analytical solutions for all the selected problems. However, FEM model fails to converge to the analytical solution for the selected problems with the time dependent transport coefficients. Finally, the developed EFGM coupled model is used to simulate groundwater flow and transport of chlorinated solvents in hypothetical and synthetic field unconfined aquifers. The EFGM solutions are compared with those from MODFLOW-RT3D simulations. The good comparison between both solutions indicates the applicability of the proposed model to multispecies transport.